Religion and environmental politics in the US House of Representatives. Issue 2 (3rd March 2016) - Newman, Brian; Guth, James L.; Cole, William; Doran, Chris; Larson, Edward J.
ABSTRACT: Does religion affect legislators' behavior on environmental policy in the US? Studies of environmental policy making have not examined this question, although the literature suggests that religion might affect legislative behavior on environmental policy. This study examines the relationship between US House members' religion and roll-call voting on environmental legislation from 1973 to 2009. It finds significant differences across religious traditions. Legislators' party and characteristics of constituencies relevant to environmental politics increasingly, but not entirely, mediate these differences.